Customary Law of the Dani Tribe in Regulating Social Life in Papua - Yonas Wenda; Debora Hubi; Elisabet Tabuni (CV. Tirta Pustaka Press, 2026)
This study examines the role of customary law of the Dani Tribe in regulating social life within indigenous communities in Papua. As one of the major indigenous groups in the Baliem Valley, the Dani Tribe maintains a strong customary legal system that functions as a living law governing social behavior, dispute resolution, kinship relations, and communal order. The research aims to analyze how Dani customary law operates in practice and how it contributes to social cohesion amid the coexistence of state law and indigenous legal systems. This research employs a qualitative socio-legal approach, utilizing primary data collected through in-depth interviews and participant observation, as well as secondary data obtained from academic literature, legal documents, and previous studies. Data were analyzed using descriptive qualitative and thematic analysis to identify patterns in the implementation and function of customary law within the Dani community. The findings reveal that Dani customary law is an unwritten, flexible, and community-based legal system enforced through social consensus and the authority of customary leaders. It plays a central role in resolving disputes through restorative justice mechanisms that emphasize reconciliation, compensation, and the restoration of social harmony. Additionally, customary law regulates kinship and marriage practices, reinforcing collective responsibility and inter-clan solidarity. Despite constitutional recognition of customary law in Indonesia, challenges remain in its integration with formal legal institutions, particularly in relation to land rights and development policies.